Detemir as a once-daily basal insulin in type 2 diabetes - Nelson SE (Dove Medical Press, 2011)
Scott E NelsonCleveland Family Medicine, Cleveland, Mississippi, USABackground: Insulin detemir, a long-acting basal insulin analog, is labeled for once-daily or twice-daily dosing in patients with type 1 (T1DM) or type 2 (T2DM) diabetes mellitus. Protocols for some earlier clinical studies of detemir evaluated twice-daily dosing, which may have generated the misperception that detemir should be prescribed twice daily for most patients. This review examines pharmacokinetic and pharmacodynamic (PK/PD), observational, and controlled studies that have evaluated once-daily and twice-daily detemir in patients with T2DM to determine the efficacy and safety of once-daily dosing.Methods: PubMed was searched using the keywords “detemir,” “once daily,” “twice daily,” and “type 2 diabetes” with the limits of clinical trial, human, and English.Results: Detemir has a relatively flat time–action profile and duration of action of up to 24 hours for patients with T2DM. Once-daily dosing is the most commonly used detemir regimen reported in observational studies, and controlled clinical studies indicate that once-daily dosing controls glycosylated hemoglobin when detemir is administered alone or in combination with a prandial insulin or oral antidiabetes drugs. In comparative clinical trials, detemir had a similar time–action profile and duration of action to another long-acting insulin analog, glargine, with less within-subject variability. Once-daily detemir was associated with no weight gain or less weight gain than comparator regimens. For patients who had not achieved glycemic control with a basal dose of once-daily detemir, adding a prandial insulin provided better glycemic control, less postprandial hypoglycemia, and a lower total daily dose of detemir than twice-daily detemir. Involvement of a multidisciplinary team and the use of a holistic approach for the treatment of T2DM patients are recommended to achieve and maintain the best patient outcomes.Conclusion: Results from PK/PD, observational, and controlled clinical studies support a once-daily detemir regimen alone or in combination with a prandial insulin or oral antidiabetes drugs.Keywords: basal insulin, detemir, type 2 diabetes mellitus, pharmacokinetics, pharmacodynamics